Effects of γ-Irradiation on the Surface and Catalytic Properties of CoO/MgO Systems Aged for One Year - G.A. El-Shobaky; S.A. El-Molla; S.A. Ismail (Adsorption Science & Technology)
The effects of γ-rays (20–160 Mrad) on the surface and catalytic properties of two Co 3 O 4 /MgO systems were investigated. The formulae of the investigated solids were 0.05Co 3 O 4 /MgO and 0.2Co 3 O 4 /MgO, respectively, both prepared by the impregnation method and calcined at 500°C. The irradiated samples were left for one year in sealed tubes before any measurements were undertaken. γ-Irradiation of the investigated solids resulted in a progressive decrease in the particle size of the Co 3 O 4 and MgO phases. This treatment also led to a measurable increase in the specific surface area of the treated solids to an extent proportional to the γ-ray dosage. Treatment of the Co 3 O 4 /MgO system with different doses of γ-rays brought about a significant increase in the catalytic activity expressed both as the reaction rate constant and as the reaction rate constant per unit surface area. However, the curve relating to the catalytic activity and dosage of γ-rays showed maxima located at 40 and 80 Mrad for samples having the formula 0.05Co 3 O 4 /MgO and 0.2Co 3 O 4 /MgO, respectively. Furthermore, samples exposed to 160 Mrad showed a larger catalytic activity than the unirradiated samples. The results demonstrate the role of γ-rays in inhibiting the deterioration of the catalytic activity of the investigated systems as a function of aging time. The irradiation process did not modify the activation energy of the catalyzed reaction but altered the concentration of active centres on the surfaces of the solids without changing their energetic nature.